Phylogeographic concordance factors quantify phylogeographic congruence among co‐distributed species in the Sarracenia alata pitcher plant system. (1st May 2016) - Satler, Jordan D.; Carstens, Bryan C.
Abstract: Comparative phylogeographic investigations have identified congruent phylogeographic breaks in co‐distributed species in nearly every region of the world. The qualitative assessments of phylogeographic patterns traditionally used to identify such breaks, however, are limited because they rely on identifying monophyletic groups across species and do not account for coalescent stochasticity. Only long‐standing phylogeographic breaks are likely to be obvious; many species could have had a concerted response to more recent landscape events, yet possess subtle signs of phylogeographic congruence because ancestral polymorphism has not completely sorted. Here, we introduce Phylogeographic Concordance Factors (PCFs), a novel method for quantifying phylogeographic congruence across species. We apply this method to the Sarracenia alata pitcher plant system, a carnivorous plant with a diverse array of commensal organisms. We explore whether a group of ecologically associated arthropods have co‐diversified with the host pitcher plant, and identify if there is a positive correlation between ecological interaction and PCFs. Results demonstrate that multiple arthropods share congruent phylogeographic breaks with S. alata, and provide evidence that the level of ecological association can be used to predict the degree of similarity in the phylogeographic pattern. This study outlines an approach for quantifying phylogeographic congruence, a central concept in biogeographic research.